2016
DOI: 10.1002/yea.3157
|View full text |Cite
|
Sign up to set email alerts
|

Maltase protein of Ogataea (Hansenula) polymorpha is a counterpart to the resurrected ancestor protein ancMALS of yeast maltases and isomaltases

Abstract: Saccharomyces cerevisiae maltases use maltose, maltulose, turanose and maltotriose as substrates, isomaltases use isomaltose, α‐methylglucoside and palatinose and both use sucrose. These enzymes are hypothesized to have evolved from a promiscuous α‐glucosidase ancMALS through duplication and mutation of the genes. We studied substrate specificity of the maltase protein MAL1 from an earlier diverged yeast, Ogataea polymorpha (Op), in the light of this hypothesis. MAL1 has extended substrate specificity and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 72 publications
2
57
0
Order By: Relevance
“…When compared with T m (65.4°C) of the levansucrase Lsc3 of Pseudomonas syringae pv. tomato [44] that was applied in this study for levan synthesis, the respective T m of BT1760 was considerably lower being comparable with respective value of the maltase protein of a yeast Ogataea polymorpha [68]. Notably, Lsc3 of P .…”
Section: Resultsmentioning
confidence: 83%
“…When compared with T m (65.4°C) of the levansucrase Lsc3 of Pseudomonas syringae pv. tomato [44] that was applied in this study for levan synthesis, the respective T m of BT1760 was considerably lower being comparable with respective value of the maltase protein of a yeast Ogataea polymorpha [68]. Notably, Lsc3 of P .…”
Section: Resultsmentioning
confidence: 83%
“…In BaAG2, a Thr is present at position of Val216 and therefore we predicted that this enzyme is most probably a maltase. However, as maltase-isomaltases also have a Thr at that position ( Figure 1, upper panel; [12,16]), based on the amino acid signature, BaAG2 may also be a promiscuous enzyme with a wide substrate spectrum like O. polymorpha MAL1. Figure 2 presents fragments of sequence comparison of BaAG2 with those of five experimentally studied maltases from GH13 family: two from bacteria, two from yeasts and one from a filamentous fungus Aspergillus.…”
Section: In Silico Analysis Of Baag2mentioning
confidence: 99%
“…In the genomes of most yeasts addressed in Viigand et al [12], the α-glucosidase genes resided in maltose utilization (MAL) clusters, whereas no MAL clusters were detected in B. adeninivorans. α-Glucosidases have been popular objects to study protein evolution and phylogenesis [13][14][15][16], but they also have a biotechnological value. Thus, some of them have a high transglycosylating activity thanks to which they produce prebiotic oligosaccharides and potential functional food ingredients such as panose, melezitose, isomelezitose and isomalto-oligosaccharides [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also compared culturing and DNA sequencing techniques to identify fungal species and suggested that cloning, cultivation, and quantitative PCR methods complemented each other, generating a more comprehensive picture of fungal content. The literature attested that the methylotrophic yeast O. polymorpha is one of the most important industrially applied yeast and could be isolated among others from soil, spoiled orange juice, leaf surfaces, exudates of plants, and insect guts (Suh & Zhou, ; Viigand, Visnapuu, Mardo, Aasamets, & Alamäe, ). The recovery of yeast species from waste workers' hands, nasal mucosa, and professional coats reinforces the need of frequent training programs inside health care institutions.…”
Section: Resultsmentioning
confidence: 99%